Entering post-otaku : approaching the Internet era in the light of otaku - Zhang, YuJia (2014)
This thesis raises a hypothesis that we have entered the Post- Otaku era. In order to prove this hypothesis, a survey has been conducted in which 30 participants gave answers regarding their Internet habits. It is said that each time when science and technology make one step forward, it increases the capacity of our organs. Compared with the impact of the industrial revolution on human beings, the influence of Internet technology seems far more tremendous as the former extends the power of our limbs while the latter enhances the competence of our brain. The significance of the present study is trying to explore the unknown future in the light of the Otaku phenomenon which is something having existed previously. The results obtained from this study reveal the fact that the daily Internet habits of many people now tend to resemble a small number of people referred to as Otaku, whose life style was viewed negatively in early stage. This finding can show us how far have we strayed away from the social norms and conventions established in the past. So viewing the Internet-oriented society in the light of Otaku can help us to obtain profound understanding of the role the Internet technology has played on the evolution of human civilization. The findings of this research might be able to throw some light on the future studies of anthropology, sociology and psychology.